Styles and Learning Results Formation Of PGSD Students in the Lecture of Learning Elementary School Problems in Even Semester 2016/2017 State University Malang - Suardana, I Made (International Research-Based Education Journal, 2019)
n the lecture of “problems of learning in elementary school” is one of the mandatory subjects for PGSD undergraduate students. This course expects students to (1) show their own performance, qualified and measurable to examine the implications of development or the implications of science, technology or art that elicits learning problems in elementary schools (SD/MI) which oriented on Active Creative Effective Fun ICT-based learning (PAKEM BATIK). (2) Master the rules and scientific ethics agree with the method of science to determine the problems of the learning system in SD/MI which oriented on PAKEM BATIK. This research purpose to describe styles and learning result formation of PGSD students. The method used descriptive qualitative. The result, there are 6 styles and learning result formation of PGSD student based on the gradation of learning skill with meaning related to observing, asking, trying, reasoning, giving, and creating.Keywords: problems, learning in elementary school, performance, qualified, and measurable